2018
DOI: 10.1016/j.ijid.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clients Strategic Index Case Testing on community-based detection of HIV infections (STRICT study)

Abstract: STRICT identifies the need for reaching out to sexual partners of index clients and providing them with HIV Testing Services (HTS) as they belong to a high risk priority population and also linking them to care and treatment. This group of people must be reached with HTS strategies in order to end the HIV epidemic as evidenced by high sero-prevalence of 51% among them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 14 publications
4
34
0
Order By: Relevance
“…However, some studies have also reported preference for other PN methods i.e. in Nigeria, where contract referral accounted for more than two-thirds of the partner referrals done [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have also reported preference for other PN methods i.e. in Nigeria, where contract referral accounted for more than two-thirds of the partner referrals done [21].…”
Section: Discussionmentioning
confidence: 99%
“…and 51%, respectively [9,12,21,25]. Furthermore, in a systematic review, the HIV prevalence among sexual partners successfully tested for HIV ranged from 12-86 % [26].…”
Section: Discussionmentioning
confidence: 99%
“…Partner services among MSM have been well taken up when implemented through alternative testing sites, using social network approaches and offering opt‐out options and multiple follow‐ups . Other studies showed that aPN services increased HIV testing and linkage to care of previously unserved partners . Qualitative investigation of preferences among FSWs suggests that aPN is particularly acceptable for contacting more “casual” and non‐primary partners and can be affordable and cost‐effective, particularly when implemented by trained lay providers .…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, UNAIDS set the goal to end the AIDS epidemic by 2030 and also stated that worldwide 95% of all people living with HIV should be aware of their HIV status while an estimated 40% still remain undiagnosed (8). HIV partner noti cation enables to identify people with undiagnosed HIV infection (9,10) and linking clients to ART (11).…”
Section: Introductionmentioning
confidence: 99%